Program wspólnoty uczącej się – nowe podejście do pojedynczego nauczyciela - Cohen-Brenner, Daphne (Studia Edukacyjne, 2017)
Promoting physics studies depends highly on the teacher’s instruction quality. This paper re-examines the influence of participation in a learning community on the teacher’s professional development. As an outcome, improving his students’ physics learning abilities, in light of theories on the process of change, is obtained thanks to the teacher participating the progra Daphne Cohen Brenner is a physics teacher and district instructor in Israel, leading a professional learning community. The article is based on the Ph.D. thesis written at AMU University in the framework of doctoral studies in education.